IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU BERDASARKAN SISTEM ZONASI DI KOTA BANDUNG - Dian Purwanti; Ira Irawati; Jossi Adiwisastra; Herijanto Bekti (LPPM Universitas Djuanda Bogor, 2019)
The new student admission based on zoning system has been implemented in Indonesia since 2017 through the Ministerial Regulation of Education and Culture No. 17/2017, then renewed by the Ministerial Regulation of Education and Culture No. 18/2018. The regulation has been enacted for the Local Office of Education in all regencies/cities in Indonesia. To be implemented, every regency and city have enacted the operational regulations in accordance with each local conditions. The Local Government of Bandung City has implemented the zoning system since 2017, namely the Regulation of Mayor of Bandung No. 553/2017 and the Regulation of Mayor of Bandung No. 456/2018. The both regulations have the different rule of game, particularly the application of quota. The zoning quota of new student admission in 2017 was regulated only for 40-50 percent, but Bandung City in 2018 applied the zoning system for 100 percent. The aims of applying the zoning system were to closely bring the students to their residences, to reduce the costs of school transportation, and to eliminate the dichotomy between the favorite and unfavorite schools. The research uses the paired sample t-Test to compare the both Mayoral Regulations and to then find the dominant factor as the cause for occuring the conflict in the process of new student admission in Bandung City. Matland’s ambiguity-conflict model is used to explain the implementation of new student admission policy. Results of the research indicate that the dichotomy of favorite and unfavorite schools can not be removed, not just because of the public mindset, but also because of the unsupporting policy of local government, and the unreadiness of local government to provide the qualified infrastructures for the education in all schools.Keywords: School Dichotomy, Policy Implementation, New Student Admission, Zoning System.